Desain Band Pass Filter Untuk Jaringan WiMAX 3.5 GHz - S, Linna Oktaviana; Valentino, Novri; Safrianti, Ery (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The development of Broadband Wireless Access (BWA) today, not only the connections that are needed, but also speed internet access and large capacity. One of the BWA technology is currently used in IEEE 802.16d WiMAX standard. IEEE 802.16d WiMAX standard using a frequency of 3.5 GHz. Indonesian satellite using the same frequency with the frequency of WiMAX. To avoid interference between WiMAX and satellite receivers need to filter WiMAX. Band pass filter is present as a solution to overcome the problem of interference between WiMAX and Satellite. In this final report discusses the design of bandstop filter circuit consisting of components - namely passive components, inductors and capacitors. Responses were used in this design is the Chebyshev response for Chebyshev response can result in a high degree of steepness of the passband to stopband.Keywords : FM Modulator, Modulated Signal, Phase Locked Loop, Carrier Signal, Information Signal.